Femoral head metastases from primary mucinous lung adenocarcinoma with left hip pain: A case report and literature review - Xue, Hang; Zhou, Wu; Zhang, Zhenhe; Panayi, Adriana C.; Xiong, Yuan; Yang, Shuhua; Mi, Bobin; Liu, Guohui; Liu, Xianzhe (Frontiers in Surgery, 2022)
Background: Primary mucinous lung adenocarcinoma, a subtype of lung adenocarcinoma, is extremely rare. Currently, as there are no specific diagnostic features, it is easy to delay the diagnosis or even to misdiagnose when atypical symptoms are present. Case summary: This case details a patient with primary mucinous lung adenocarcinoma and metastasis to the femoral head. The sole symptom was left hip pain and the initial diagnosis was isolated femoral head necrosis. Conclusions: By presenting this rare case report and the experiences learned from it, we hope to assist clinicians to identify bone metastasis cases with non-typical symptoms in order to make the correct diagnosis as soon as possible.